FAKTOR-FAKTOR YANG MEMPENGARUHI MASYARAKAT NON MUSLIM MENABUNG DI PT. BANK SYARIAH MANDIRI - NOVA SYAFRINA; SUDARMIN MANIK (JEBI (Jurnal Ekonomi dan Bisnis Islam), 2018)
The theme of the article is a business based on the principles of Islamic economics. The purpose of this study is to determine the factors that influence non-Muslim society to save in sharia bank. The population in this study is non-muslin customers in Bank Syariah Mandiri Cabang Duri is 3,579 people. And the sample amounted to 97 people by using sampling technique that is random sampling. Data analysis was performed by using reliability test, multiple linear regression, R2 test, F test and t test. The test is conducted in order to determine the factors that influence non-Muslim community to save in sharia bank. Based on the result of research that competence with value adjusted R square can be 0,502, meaning factor of facility, promotion and product contributed 50,2% to non customer's decision, facility and product have positive effect while promotion has negative effect. Based on significant level of promotion and product have significant effect but facility not significant to decision of non Muslim customer to save in sharia bank. In the simultaneous test (Test F) that the variables X significantly affect the variable Y with a significance level of 0.000. The conclusion from the research that this research hypothesis can be accepted truth.